Physiological and Medical Aspects That Put Women Soldiers at Increased Risk for Overuse Injuries. (November 2015) - Epstein, Yoram; Fleischmann, Chen; Yanovich, Ran; Heled, Yuval
Abstract : Abstract: Epstein, Y, Fleischmann, C, Yanovich, R, and Heled, Y. Physiological and medical aspects that put women soldiers at increased risk for overuse injuries. J Strength Cond Res 29(11S): S107–S110, 2015—Anthropometric and physiological factors place female soldiers at a disadvantage relative to male soldiers in most aspects of physical performance. Average aerobic and anaerobic fitness levels are lower in women than in men. Thus, women have a lower overall work capacity and must exert themselves more than men to achieve the same output. The lower weight and fat-free mass and the higher body fat of women are associated with lower muscle strength and endurance, placing them at a disadvantage compared with men in performing military tasks such as lifting and carrying weights, or marching with a load. Working at a higher percentage of their maximal capacity to achieve the same performance levels as men, women tire earlier. Their smaller size, skeletal anatomy, and different bone geometry also predispose women to a higher incidence of exercise-related injuries. Consequently, the attrition rate of female soldiers in combat units is higher than that of their male counterparts. This review summarizes the literature on gender-related physiological and anatomical differences that put female soldiers at an increased risk of exercise-related injuries.